AB0985 Persistence and adverse events in patients treated with denosumab. (12th June 2018) - Lopez, A.; Janta, I.; Nieto, J.C.; Martinez Barrio, J.; Serrano, B.; Garcia, F.; Sanchez, J.C.; Garaballu, C.; Del Rio, T.; Gonzalez, C.; Lopez Longo, J.; Monteagudo, I.
Abstract : Background: Denosumab (DNS) is a human monoclonal antibody directed against RANKL, which blocks the maturation of the osteoclast, inhibiting bone resorption. The binding of DNS to RANKL suppresses bone resorption mediated by osteoclasts and decreases bone turnover. Objectives: To evaluate the survival rate of DNS, adverse events and reasons for the DNS discontinuation. Methods: This was a prospective observation study in patients with OP which initiated treatment with DNS between January 2013 and December 2017. Patients included were followed up in the Rheumatology Nurse Clinic every six month. Demographics date, disease features, concomitant disease and treatments, adverse events and reasons for discontinuation were collected. Results: We included 220 patients (80.5% women) with a mean age (range, SD) of 67.19 (30–89, 11.2) years. In average (range, SD), patients received 3.85 (1–11, 2.2) doses of DNS, with a mean duration of treatment (range, SD) of 23.03 (6–66, 13.3) months. 191 (86.8%) patients received also treatment with calcium and vitamin D supplements. Before the start of the treatment with DNS, 123 (55.9%) patients had received another specific treatment for OP with mean previous treatment duration of 51.6 months. Previous fragility fractures were reported in 150 (68.1%) patients, of whom 91 (41.3%) patients had two or more fractures before starting treatment with DNS. Of all included the patients, 108 (49%) patients had an inflammatory autoimmune disease (IAD) diagnosed. In addition, 100 (45.4%) patients had concomitant biological and/or synthetic treatment and 77 (35%) patients received concomitant treatment with corticosteroids. During the treatment with DNS, 30 (13.6%) patients had new fractures, 5 (2.3%) patients had 2 fractures. Eleven fractures were vertebral, 3 of femur, one of radius and 21 other locations. There were no differences between patients with or without glucocorticoid treatment (0.234). The most frequent adverse events (AE) were infections in 88 (40%) patients, muscle pain in 15 (0.6%) patients, fatigue in 7 (0.31%) patients, itching, heat and fever in 2 (0.9%) patients and osteonecrosis of the jaw in 2 (0.9%) patients. The 2 patients with osteonecrosis of the jaw had previous treatment with bisphosphonates for more than 24 months. At 60 months, 185 (84.1%) patients continued with DNS. In 37 (1.6%) patients, DNS was discontinued; in 4 patents DNS was restarted. The reasons for suspension were hypercalciuria 1 (0.04%), hypocalcemia 1 (0.04%), local hypersensitivity reactions 4 (0.18%), normalisation of BMD 5 (0.2%), dental problems 11 (0.4%) and others 17 (0.7%). The mean (SD, 95% CI) of DNS survival was 51.2 (1.9; 47.3–55.1) months. There are no differences in the survival rates of DNS between patients with and without concomitant biologic therapy (p=0.995). Conclusions: The majority of patients who started treatment with DNS continue the treatment with good tolerance. The most frequent adverse effects were infections but they have not led to suspension of treatment. Disclosure of Interest: None declared